Study on Peripheral Central Venous Catheter Induced Supraventricular Tachycardia in a Patient of Acute Lymphoblastic Leukemia - Rangraze, Imran Rashid; Abdulrahman, Asiri; Ali, Al-Hanash; Khan, Shehla Shafi (Current Topics in Medicine and Medical Research Vol. 12, 2021)
Central venous catheters (CVCs) are used in intensive care units (and, increasingly, in other locations) to administer intravenous fluids and blood products, drugs, parenteral nutrition, and to monitor haemodynamic status. Numerous complications like ventricular dysrhythmias and bundle branch block are well recognized complications during central venous access procedures, as was the case with our patient. The risk of complication during the insertion or exchange of central venous catheters has been well documented. The majority of complications involve mechanical problems, although rarely it may induce arrhythmias as well [1]. Herein we present a case of peripheral central venous catheter induced supraventricular tachycardia in a young patient of acute lymphoblastic leukemia.